2018
DOI: 10.1101/400267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for the Modulation of the Immune Response in Peripheral Blood Mononuclear Cells after Stimulation with a High Molecular Weight β-glucan Isolated fromLactobacillus fermentumLf2

Abstract: 27Lactobacillus fermentum Lf 2 produces large amounts of exopolysaccharides under 28 optimized conditions (~2 g/L, EPS) which have been shown to possess 29 immunomodulatory activity. In this study, the crude EPS was fractionated to give a 30 high molecular weight (HMw) homoglycan and a mixture of medium molecular 31 weight heteroglycans. The HMw EPS was isolated and identified as a -glucan. 32 Peripheral blood mononuclear cells (PBMC) were pre-treated with purified 33 polysaccharide to determine if the HMw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This has been confirmed by studies showing that phosphate is the molecule that triggers the immune response, as chemical dephosphorylation of these HePS leads to a decrease in the stimulatory effect [ 168 , 171 , 190 , 194 , 195 ]. However, immunomodulatory activity has also been associated with high molecular weight HePS, which appears to suppress the immune response [ 168 , 171 , 185 , 190 , 196 , 197 , 198 ]. In addition, the monosaccharide composition of EPS has been shown to influence its anti-inflammatory properties, possibly by association with the recognition of receptors on the surface of immune cells [ 199 , 200 ].…”
Section: Health-promoting Effectsmentioning
confidence: 99%
“…This has been confirmed by studies showing that phosphate is the molecule that triggers the immune response, as chemical dephosphorylation of these HePS leads to a decrease in the stimulatory effect [ 168 , 171 , 190 , 194 , 195 ]. However, immunomodulatory activity has also been associated with high molecular weight HePS, which appears to suppress the immune response [ 168 , 171 , 185 , 190 , 196 , 197 , 198 ]. In addition, the monosaccharide composition of EPS has been shown to influence its anti-inflammatory properties, possibly by association with the recognition of receptors on the surface of immune cells [ 199 , 200 ].…”
Section: Health-promoting Effectsmentioning
confidence: 99%
“…The results from both cytokine and NO production inhibition, showed an anti-inflammatory activity of PCL 2 /Glu NPs which contrasts with all other PCL-based NPs. As β-glucans are widely reported in the literature to induce TNF-α release in PBMCs, the fact that PCL 2 /Glu NPs did not induce TNF-α production, and even inhibited its release when stimulated by LPS was a surprising result. However, this phenomenon has been previously reported.…”
Section: Resultsmentioning
confidence: 95%
“…composition of the EPS and in characterising the polysaccharides present. In an earlier study, we reported that the crude EPS contains a mixture of both high and medium molecular mass polysaccharides and identified the high molecular mass polysaccharide (HMMP) as a glucan, which presented biological activity [22]. In this paper, we report the characterisation of the medium molecular mass polysaccharides (MMMP).…”
Section: Introductionmentioning
confidence: 94%
“…The sample eluted as two main peaks: HMMP eluted in the early fractions and MMMP eluted in tubes 25-30. The characterisation of the structure of the HMMP has already been reported [22]. USA) was used for the data analysis.…”
Section: Nmr Analysis Of the Sd-mmmpmentioning
confidence: 99%
See 1 more Smart Citation